A Functional Material Based Heterojunction Diode - El-Nasser, H. M.; Mensah-Darkwa, K.; Al-Senany, Norah; Al-Ghamdi, Ahmed; Gupta, R. K.; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Springer, 2018)
In this study, the phosphotungstic acid/p-Si diode was fabricated by a drop coating method. The fabricated diode had excellent rectifying properties. The electrical properties of the diode were investigated in the temperature range of 50-400 K. The optical band gap of the phosphotungstic acid film was determined and found to be 3.66 eV. The electrical and photoresponse properties of an Al/p-Si- phosphotungstic acid/Al photodiode were studied. The electronic parameters such as ideality factor (n), barrier height (Phi(B)) and series resistance (R-s) were found to be strongly temperature dependent.
Keywords: Phosphotungstic acid; Photodiode; Ideality factor; Barrier height